Effects of AVE2268, a Substituted Glycopyranoside, on Urinary Glucose Excretion and Blood Glucose in Mice and Rats - Bickel, Martin; Brummerhop, Harm; Frick, Wendelin; Glombik, Heiner; Herling, Andreas Waldemar; Heuer, Hubert Otto; Plettenburg, Oliver; Theis, Stefan; Werner, Ulrich; Kramer, Werner (Arzneimittelforschung, 2008)
AVE2268, a substituted glycopyranoside, is an orally active and selective inhibitor of sodium-dependent glucose transporter 2 (SGLT2; IC50=13 nmol/L). Investigation of the pharmacological profile of AVE2268 on urinary glucose excretion (UGE) and blood glucose after glucose challenge (po or intraperitoneal) was performed in mice and rats. AVE2268 caused a dose-dependent increase of UGE in mice (ID30 = 79 ± 8.1 mg/kg p.o.) and rats (ID30 = 39.8 ± 4.0 mg/kg p.o.). AVE2268 in mice was more potent to decrease blood glucose ascent when glucose was given intraperitoneally (ID50 = 13.2 ± 3.9 mg/kg), compared to orally administered glucose (ID50 = 26.1 ± 3.9 mg/kg), showing that AVE2268 has no effects on SGLT 1 in the gut in vivo, which is in accordance with ist very low affinity to the SGLT 1 in vitro (IC50 >10,000 nmol/L). During an oral glucose tolerance test, AVE2268 dosedependently increased UGE, with subsequent decreases of AUC and blood glucose. A highly significant inverse correlation between AUC and UGE was found (p<0.001). The increase in UGE is linked to the inhibition of SGLT2 only. This profile renders AVE2268 as a new antidiabetic drug for the treatment of type 2 diabetes.
Keywords: Antidiabetic agents; AVE2268, effect on blood glucose, mouse, rat; Glucose, renal filtration, sodium-dependent glucose transporter 2, urinary excretion; Glycopyranoside, substituted; Phlorizin